2022
DOI: 10.3390/biom12091303
|View full text |Cite
|
Sign up to set email alerts
|

Co-Stimulatory Receptor Signaling in CAR-T Cells

Abstract: T cell engineering strategies have emerged as successful immunotherapeutic approaches for the treatment of human cancer. Chimeric Antigen Receptor T (CAR-T) cell therapy represents a prominent synthetic biology approach to re-direct the specificity of a patient’s autologous T cells toward a desired tumor antigen. CAR-T therapy is currently FDA approved for the treatment of hematological malignancies, including subsets of B cell lymphoma, acute lymphoblastic leukemia (ALL) and multiple myeloma. Mechanistically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 238 publications
0
10
0
Order By: Relevance
“…Intriguingly, most uterine γδ T cells expressed activation marker CD25, about 70% [ 10 ] but not CD4 + T and CD8 + T cells. CD4 + T and CD8 + T cells in uterus expressed much lower levels of costimulatory receptors CD27 which is involved in the regulation of T cell activation, especially in T cell memory [ 26 , 27 ]. These may indicate uterine γδ T cells and αβ T cells play different roles in intrauterine immune microenvironment with the latter favoring maternal–fetal tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, most uterine γδ T cells expressed activation marker CD25, about 70% [ 10 ] but not CD4 + T and CD8 + T cells. CD4 + T and CD8 + T cells in uterus expressed much lower levels of costimulatory receptors CD27 which is involved in the regulation of T cell activation, especially in T cell memory [ 26 , 27 ]. These may indicate uterine γδ T cells and αβ T cells play different roles in intrauterine immune microenvironment with the latter favoring maternal–fetal tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This approach stimulates cytokine production, sustaining the anti-tumor immune response, and fostering improved overall patient survival. [ 37 ] Honikel and Olejniczak [ 36 ] showed that illuminating the significance of CD28 allows an understanding of its role as a potent costimulatory signal for T-cell activation and function. The interactions between CAR design and T-cell biology outline the therapy’s multifaceted effectiveness in combating MM.…”
Section: Discussionmentioning
confidence: 99%
“…Co-stimulation has long been known to be critical for anti-tumor effects of CAR T cells 83,84 , with different CAR-encoded co-stimulatory domains having distinct effects on CAR T cell properties 17 . Clinically available CARs contain either a CD28 or a 4-1BB co-stimulatory domain.…”
Section: Car T Cell Therapies Targeting Bcma Have Shown Curative Pote...mentioning
confidence: 99%